Noninvasive assessment of cardiac output by brachial occlusion-cuff technique: comparison with the open-circuit acetylene washin method - Sajgalik, Pavol; Kremen, Vaclav; Carlson, Alex R; Fabian, Vratislav; Kim, Chul-Ho; Wheatley, Courtney; Gerla, Vaclav; Schirger, John A; Olson, Thomas P; Johnson, Bruce D (Journal of applied physiology (Bethesda, Md., 2016)
Cardiac output (CO) assessment as a basic hemodynamic parameter has been of interest in exercise physiology, cardiology, and anesthesiology. Noninvasive techniques available are technically challenging, and thus difficult to use outside of a clinical or laboratory setting. We propose a novel method of noninvasive CO assessment using a single, upper-arm cuff. The method uses the arterial pressure pulse wave signal acquired from the brachial artery during 20-s intervals of suprasystolic occlusion. This method was evaluated in a cohort of 12 healthy individuals (age, 27.7 ± 5.4 yr, 50% men) and compared with an established method for noninvasive CO assessment, the open-circuit acetylene method (OpCirc) at rest, and during low- to moderate-intensity exercise. CO increased from rest to exercise (rest, 7.4 ± 0.8 vs. 7.2 ± 0.8; low, 9.8 ± 1.8 vs. 9.9 ± 2.0; moderate, 14.1 ± 2.8 vs. 14.8 ± 3.2 l/min) as assessed by the cuff-occlusion and OpCirc techniques, respectively. The average error of experimental technique compared with OpCirc was -0.25 ± 1.02 l/min, Pearson's correlation coefficient of 0.96 (rest + exercise), and 0.21 ± 0.42 l/min with Pearson's correlation coefficient of 0.87 (rest only). Bland-Altman analysis demonstrated good agreement between methods (within 95% boundaries); the reproducibility coefficient (RPC) = 0.84 l/min with R2 = 0.75 at rest and RPC = 2 l/min with R2 = 0.92 at rest and during exercise, respectively. In comparison with an established method to quantify CO, the cuff-occlusion method provides similar measures at rest and with light to moderate exercise. Thus, we believe this method has the potential to be used as a new, noninvasive method for assessing CO during exercise.
Keywords: dospělí; Female; brachial cuff; occlusion; Cardiac Output; Adult; ženské pohlaví; Rest; arteria brachialis; Reproducibility of Results; lidé; cvičení; cardiac output; odpočinek; acetylen; krevní tlak; reprodukovatelnost výsledků; Acetylene; Male; noninvasive; mužské pohlaví; Blood Pressure; Exercise; Brachial Artery; minutový srdeční výdej; Humans